Prospects of Hydrogels in Agriculture for Enhancing Crop and Water Productivity under Water Deficit Condition. (22nd June 2022) - Patra, Sanmay Kumar; Poddar, Ratneswar; Brestic, Marian; Acharjee, Pravat Utpal; Bhattacharya, Parijat; Sengupta, Sudip; Pal, Payel; Bam, Nyape; Biswas, Barun; Barek, Viliam; Ondrisik, Peter; Skalicky, Milan; et al.
Abstract : In arid and semiarid regions and under rainfed conditions, water availability is one of the principal ecological constraints that hinder agriculture's sustainability. The super absorbent polymer (agricultural) is water-absorbing and is cross-linked to absorb aqueous solutions through bonding with water molecules. It is a new approach to water management under water-stressed conditions to conserve soil moisture in the active rooting zone of crops by reducing the evaporation, deep percolation, and runoff losses. Agricultural hydrogels are water retention granules which swell their original size to numerous intervals when they come in contact with water. It can absorb and retain a huge amount of moisture under plentiful rainfall and irrigation events and release it back to the soil for mitigating crop water demand when the rhizosphere zone dries up under drought conditions. It plays multifarious roles in agriculture including soil-water retainer, nutrient and pesticide carriers, seed coating, soil erosion reducer, and food additives. It has the extraordinary ability in improving different physicochemical, hydrophysical, and biological properties of soil, simultaneously decreasing irrigation frequency, enhancing the water and nutrient use efficiencies, and increasing the yield and quality of the field, plantation, ornamental, and vegetable crops. These biodegradable materials are nontoxic to the soil, crop, and environment. Hence, the addition of the hydrogel polymer will be a promising and feasible technological tool for augmenting crop productivity under moisture stressed conditions.